Growing culture of illegal dentistry globally,including Malaysia. calling for multidisciplinary action for patient safety - Che Musa, Muhd Firdaus; Hassan, Yang Rafidah (Journal of Biotechnology and Strategic Health Research, 2019)
Illegal dentistry is a term used to describe any dental procedures done by bogus, unqualified dentists who perform various dental procedures without proper educational background. The issues of illegal dentistry had gone worldwide; not only involving the emerging of illegal practitioners but also raises concerns over the authenticity of dental equipment being used and available in the global market. This necessitates the interaction between the professions, public and dental suppliers. A qualified dentist is strictly recommended to continuously liaise with licensed dental dealers in order to get a constant supply of genuine dental products and equipment for their clinics. In Malaysia, a well-trained, qualified dentist is required to register to ensure they are committed in ensuring a professional, safe, high quality and ethical dental practice. The public must be able to identify the authenticity of a practitioner’s academic claims by examining their practice and checking whether they are registered to ensure they all possess a license in good standing and that their educational claims are authentic.